Impact of the crisis on working conditions in Europe - European Foundation for the improvement of living and working conditions. (Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2013)
The economic and financial crisis is affecting working conditions across EU Member States and Norway in different ways and scope. Yet the pattern is of less work, reduced overall working time, less overtime, rising job insecurity, less choice for workers, wage freezes and wage cuts. There is also greater work intensity, deterioration of work-life balance, increasing stress at work, greater risk of harassment/bullying, less absenteeism, growth in the informal economy and changes to migration patterns. This report ranks countries by changes in working conditions since the crisis began based on country averages for defined indicators: job insecurity, involuntary temporary employment, involuntary part-time working, net migration, work-life balance, work intensity, absenteeism, work accidents and job satisfaction. Average trends can hide composition effects, while the crisis has not had the same effect on all groups of workers.